(untitled) (Research, Society and Development, 2021)
Benzodiazepines are drugs that act as depressants of the Central Nervous System, have anticonvulsant, muscle relaxant, sedative and hypnotic action. These drugs have been massively prescribed for years, but without the recommended dosage care, which leads to their indiscriminate use, resulting in exposure to toxicological risks. Thus, this article discusses, through an integrative literature review, the indiscriminate use of benzodiazepines and the pharmacist’s contribution to a rational use. The study was descriptive-observational, having as methodology the integrative literature review. The Virtual Health Library, Online Scientific Electronic Library and Academic Google were selected as database. 18 articles were relevant to the research, where it was noticed that the administration of these drugs is done mainly by the elderly and women, related to social issues and that most cases of abusive use occur due to lack of information from medical professionals and pharmacists. In this sense, the influence of the pharmacist in combating abusive use, correlated with the profession’s code of ethics, will act in the analysis of cases of indiscriminate use, and may indicate the suspension of medication, as well as raising awareness in the community and suggesting non-pharmacological alternatives.